Stoneley waves in a non-homogeneous orthotropic granular medium under the influence of gravity - S. M. Ahmed (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to investigate the Stoneley waves in a non-homogeneous orthotropic granular medium under the influence of a gravity field. The frequency equation obtained, in the form of a sixth-order determinantal expression, is in agreement with the corresponding result when both media are elastic. The frequency equation when the gravity field is neglected has been deduced as a particular case.